CELIAC DISEASE AS A FAMILY ILLNESS: AN ANALYSIS OF EMOTIONAL BURDEN, LIFESTYLE CHANGES, AND THE ROLE OF MODERN SUPPORT TECHNOLOGIES WITHIN THE FAMILY SYSTEM - A NARRATIVE REVIEW - Paulina Jarząbek; Radosław Gryko; Aleksandra Włodarczyk; Norbert Grabias; Jędrzej Piotrowski; Maria Rajkowska; Julia Weronika Mieszkowska; Bernard Myszewski; Anna Kinga Tejchma; Łukasz Dominik Woźniak (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Celiac Disease (CD) necessitates strict, lifelong adherence to a gluten-free diet (GFD), transforming a clinical diagnosis into a pervasive "family illness." This condition imposes profound emotional, logistical, and financial strains on the entire household. Caregivers frequently encounter states of "hypervigilance" and social withdrawal, while patients navigate complex socio-economic hurdles. Aim of the Study: This narrative review aims to analyze the multidimensional impact of CD on the family unit, focusing on emotional distress, lifestyle modifications, and socio-economic challenges. Furthermore, it evaluates the efficacy of emerging technologies, including mHealth, AI, e-learning, and portable sensors - in facilitating family adaptation and disease management. Methodology: A comprehensive review of literature from PubMed and Google Scholar was conducted, prioritizing peer-reviewed articles published between 2018 and 2025. The analysis synthesized key themes regarding family Quality of Life (QoL), the economic implications of the GFD, and the utility of digital support tools. Results: Families managing CD experience elevated psychological distress, characterized as a "ripple effect" that disrupts domestic dynamics and spontaneity. Economic data confirms a "double burden": gluten-free products are up to 183% more expensive yet often nutritionally inferior to standard alternatives. While digital innovations like mobile apps and e-learning significantly enhance self-management and psychosocial well-being, challenges remain regarding the reliability of portable sensors, unverified online information, and the digital divide. Conclusions: Effective CD management requires a paradigm shift from patient-centered to family-centered care. Modern technologies offer vital support for the transitioning to patient autonomy but require professional oversight to mitigate anxiety. Addressing the socio-economic and nutritional disparities of the GFD constitutes an urgent public health priority.